Desain dan Konstruksi Website Profil Program Studi Teknik Informatika Menggunakan Sistem Manajemen Konten Wordpress - Rizki Ananda Pratama; Rasiban (Jurnal Nasional Teknologi Komputer, 2021)
This article explores the creation of a study program profile website using the WordPress Content Management System (CMS). In higher education, there's a need to provide current and relevant information to prospective students, existing students, faculty, and the general public. A study program profile website serves as an effective means to fulfill this requirement. The design process outlined in this research includes conducting a needs analysis, designing the interface, choosing a suitable WordPress theme, developing features specific to the study program, and testing the website’s functionality. Utilizing WordPress as a content management platform allows for easy content management and updates without the need for advanced programming skills. The outcome of this research is a responsive, visually appealing, and user-friendly study program profile website. Features include details about study programs, curriculum, faculty, facilities, and the latest news, along with a search function to help users find specific information quickly. Adopting the WordPress CMS not only enhances time and cost efficiency in website management but also offers flexibility in updating or modifying content, ensuring that the information remains current and relevant. In summary, the design of a study program profile website using WordPress CMS proves to be an effective approach for delivering timely and pertinent information to stakeholders in the academic sector. This research contributes to the field of information technology, particularly in leveraging CMS platforms for effective content management within higher education.